Extent of Community Participation in the Decision-Making and Planning Processes for Sustainable Development Projects in Bauchi South Senatorial Zone, Bauchi State - Kyamru, James Iliya; Jarmai, Y; Mudi, H; Ali, U (International Journal of Human Kinetics, Health and Education, 2023)
The study investigated extent of community participation in the decision-making and planning processes for sustainable development projects in Bauchi South Senatorial zone, Bauchi State. Two research questions and two hypotheses guided the study. The study adopted a descriptive cross-sectional survey research design. Population for the study consisted of 1,503 members of the registered 46 Community Development Associations (CDAs) in Bauchi South Senatorial Zone. A two-stage sampling procedure was used to draw a sample size of 316 registered CDAs members. The instrument used for data collection was a structured questionnaire. All the research questions were analysed using mean and standard deviation. The hypotheses were tested using t-test statistics at .05 level of significance. Findings show that overall, members of the community participated in the decision making and planning processes for sustainable community development projects in Bauchi South Senatorial Zone, Bauchi State to a moderate extent. Gender had no influence on the extent members of the community participated in the decision making and planning processes for sustainable community development projects in Bauchi South Senatorial Zone, Bauchi State (p < .05). The findings suggested that government should organize seminars and workshops for community members; these will help in influencing the attitudes and orientation of community members to participate in a community development project that has direct bearing on the community, therefore to alleviate problems the community encounters in general.